Accuracy of 3D Printed Implant Casts Versus Stone Casts: A Comparative Study in the Anterior Maxilla. Issue 9 (3rd February 2021) - Banjar, Ayman; Chen, Yo‐wei; Kostagianni, Aikaterini; Finkelman, Matthew; Papathanasiou, Aikaterini; Chochlidakis, Konstantinos; Papaspyridakos, Panos
Abstract: Purpose: To conduct an in vitro comparison of the amount of three‐dimensional (3D) deviation of 3D printed casts generated from digital implant impressions with an intraoral scanner (IOS) to stone casts made of conventional impressions. Material and Methods: A maxillary master cast with partially edentulous anterior area was fabricated with two internal connection implants (Regular CrossFit, Straumann). Stone casts (n = 10) that served as a control were fabricated with the splinted open‐tray impression technique. Twenty digital impressions were made using a white light IOS (TRIOS, 3shape) and the Standard Tesselation Language (STL) files obtained were saved. Based on the STL files, a digital light processing (DLP) and a stereolithographic (SLA) 3D printer (Varseo S and Form 2) were used to print casts (n = 10 from each 3D printer). The master cast and all casts generated from each group were digitized using the same IOS. The STL files obtained were superimposed on the master cast STL file (reference) to evaluate the amount of 3D deviation with inspection software using the root mean square value (RMS). The independent‐samples Kruskal‐Wallis test and Dunn's test with Bonferroni correction (for post hoc comparisons) were used for statistical analyses. Results: The Varseo S group had the lowest median RMS value [77.5 µm (IQR = 91.4‐135.4)], followed closely by the Conventional group [77.7 µm (IQR = 61.5‐93.4)]. The Form 2 had the highest mean value [98.8 µm (IQR = 57.6‐87.9)]. The independent‐samples Kruskal‐Wallis test revealed a significant difference between the groups ( p = 0.018). Post hoc testing revealed a significant difference between Varseo S and Form 2 ( p = 0.009). Conclusion: The casts generated from the Varseo S 3D printer had better 3D accuracy than did those from the Form 2 3D printer. Both the Varseo S group and the conventional stone casts groups had similar 3D accuracy.